THE EFFECT OF FREQUENCY WATER ON BIOMASS AND GROWTH PAGODA MUSTARD (BRASSICA RAPA SUBSP NARINOSA) IN DRIP IRRIGATION SYSTEMS - Nadi Prabowo, Candra
Global air temperature has increased by about 0.15oC – 0.3oC every decade. The increase in global temperature can result in a reduction in water potential for agricultural cultivation, including in Indonesia. Drip irrigation is irrigation with low pressure and water supply system that is applied only to the area around plant roots. This study looked at three factors, namely the yield of biomass, growth, and plant mass balance of Sawi Pagoda (Brassica narinosa). Biomass yield parameters include wet weight, dry weight, moisture content, and harvest index. The growth parameters studied included plant height, number of leaves and canopy area of Pagoda Mustard (Brassica narinosa). Parameters of mass balance include crop water productivity and mass calculation of Pagoda Mustard (Brassica narinosa) plants. The study was conducted using a completely randomized design (CRD) with a frequency of watering 1 time a day, 2 times a day, 5 times a day and 7 times a day. This research resulted in the treatment of watering frequency that did not affect the three factors but the highest value was the plant height growth parameter is 14,8 cm; number of leaves is 65 leave; canopy area is 472.57 cm2. Then in the biomass yield parameter, the wet weight is 129 g; dry weight is 7.1 g; water content is 94.14%; and a harvest index is 0.73. Meanwhile, the mass balance parameters obtained crop water productivity 37.94 kg/m3; mass balance in a state of equilibrium by having a total mass balance of 3,740.62 g/polybag/production; input energy is 25,686.71 kJ/production and photosynthesis output energy is 1,284.34 kJ/production, metabolism is 4,880.47 kJ/production and evapotranspiration is 6,325.74 kJ/production so that the heat loss from the production system is 13,196.15 kJ/production.